Selective inhibition of local excitatory synaptic transmission by serotonin through an unconventional receptor in the CA1 region of rat hippocampus - Mlinar, Boris (Blackwell Science Inc, 2001)
1. The modulation of synaptic transmission by serotonin (5-HT) was studied using whole-cell voltage-clamp and sharp-electrode current-clamp recordings from CA1 pyramidal neurones in transverse rat hippocampal slices in vitro. 2. With GABA(A) receptors blocked, polysynaptic transmission evoked by stratum radiatum stimulation was inhibited by submicromolar concentrations of 5-HT, while monosynaptic excitatory transmission and CA1 pyramidal neurone excitability were unaffected. The effect persisted following pharmacological blockade of 5-HT(1A) and 5-HT(4) receptors, which directly affect CA1 pyramidal neurone excitability. 3. Concentration-response relationships for 5-HT were determined in individual neurones; the EC(50) values for block of polysynaptic excitation and inhibition by 5-HT were ≈230 and ≈160 nm, respectively. The 5-HT receptor type responsible for the observed effect does not fall easily into the present classification of 5-HT receptors. 4. 5-HT inhibition of polysynaptic EPSCs persisted following complete block of GABAergic transmission and in CA1 minislices, ruling out indirect effects through interneurones and non-CA1 pyramidal neurones, respectively. 5. Monosynaptic EPSCs evoked by stimulation of CA1 afferent pathways appeared to be unaffected by 5-HT. Monosynaptic EPSCs evoked by stimulation of the alveus, which contains CA1 pyramidal neurone axons, were partially inhibited by 5-HT. 6. We conclude that 5-HT inhibited synaptic transmission by acting at local recurrent collaterals of CA1 pyramidal neurones. This may represent an important physiological action of 5-HT in the hippocampus, since it occurs over a lower concentration range than the 5-HT effects reported so far.